Spatial-temporal evolution and prediction of carbon storage in Mohe city by linking the logistic-CA-Markov and InVEST models - Yan, Xuan; Li, Miao; Guo, Dianfan; Yang, Dongyu; Zhan, Daqing (Frontiers in Earth Science, 2024)
Carbon storage plays a vital role in the provision of ecosystem services, and the alteration of land use has a profound influence on the carbon storage capacity of ecosystems. Therefore, it is of great significance to investigate land use/cover change (LUCC) and its impact on ecosystem carbon storage under different scenarios to achieve "carbon neutrality" in the region. This study specifically focuses on the city of Mohe city, China, utilizing multi-source data and comprehensive ecological modeling approaches to assess and analyze the temporal and spatial trends as well as the driving factors of carbon storage in Mohe city, China from 1980 to 2040. The results indicated that: (1) From 1980 to 2020, there was a decline in the area of farmland, forest, and water, while grassland, urban land, and wetland experienced an increase. Additionally, when comparing the Nature Evolution Scenario (NES) with the Ecological Conservation Scenario (ECS), it was observed that the ECS exhibited ecological benefits, including a slight increase in forested area and limited expansion of urban land from 2020 to 2040. (2) Mohe City suffered a severe cumulative carbon loss of 4.04Tg from 1980 to 2020. In the period of 2020-2040, under the NES, the projected carbon loss is estimated to be 1.02Tg, whereas the ECS shows a slight increment of 0.2Tg in carbon storage. (3) Apart from LUCC, mean annual precipitation and population density are the two most significant factors affecting the spatial differentiation variability of carbon storage. The interactions of mean annual precipitation and population density with other factors exhibit a non-linear enhancement, which had a coefficient of 21.91%. Moreover, the combination of any two environmental factors increased this power.. This study contributes to a deeper understanding of the relationship between LUCC and carbon storage due to natural environmental and socioeconomic factors.